Arabic Curriculum Development through Arabic Debate Competitions in the Language Festival at PMDG Putri Campus 1 - Fairuz subakir; Agus Yasin; Ahmad Ario Sofian; Nur Fera Khalifah; Nuraeni Rahmawati (CV Putra Publisher, 2025)
This study investigates the role of Arabic Debate Competitions in the Language Festival as a strategy for Arabic curriculum development at PMDG Putri Campus 1. The research employed a qualitative case study design to explore how debate activities contributed to communicative language learning, curriculum enrichment, and the strengthening of institutional language culture. Data were collected through observation, semi-structured interviews, and documentation involving language supervisors, debate coaches, organizing committee members, and participating students. The findings reveal that the Arabic Debate Competition functioned as an experiential and performance-based learning activity that integrated speaking, listening, vocabulary mastery, critical thinking, and argumentative reasoning within authentic communication contexts. The competition also strengthened students’ confidence, public speaking ability, teamwork, and active Arabic language use beyond classroom settings. Furthermore, the program contributed significantly to reinforcing bi’ah lughawiyyah and supporting competency-based curriculum implementation in pesantren education. This study concludes that Arabic debate activities can serve as an effective curriculum development strategy by connecting formal language instruction with interactive linguistic practices and character education. The findings contribute to the discourse on Arabic curriculum innovation in Islamic boarding school education and provide practical implications for integrating communicative extracurricular programs into Arabic language learning systems.